An eye movement analysis of web usability: Differences between older adults with and without mild cognitive impairment. Issue 2 (15th March 2018) - Haesner, Marten; Chandra, Johan; Steinert, Anika; Steinhagen-Thiessen, Elisabeth
ABSTRACT: Older adults are exposed to computer-based applications daily. However, most websites and applications are not specifically developed for older adults. Studies have shown that older adults with mild cognitive impairment (MCI) behave differently from older adults without MCI in website usage. Eye tracking is a valuable tool to assess users' eye movement behavior in relation to website usability. Understanding the differences in web navigational behavior between older adults with and without MCI would be helpful for developing websites for this target group. This article presents eye tracking data from several tasks while using a cognitive training application. Overall results revealed that older adults with MCI required significantly longer to complete the tasks ( U  = 116.0, p  < 0.05) and were significantly less successful in completing the tasks than those without MCI ( U  = 101.5, p  < 0.05). However, there were no significant differences in eye movement patterns for any of the individual tasks, except one that required participants to use several pathways in order to successfully complete it. These findings demonstrate that eye tracking is an effective method for accessing users' eye movement patterns and the usability of a platform. However, the method was not successful in differentiating eye movement behavior between older adults with and without MCI.